The urgency of multiculturalism in the curriculum according to Kenneth T. Henson in Indonesian education - Abdul Karim Suhadha; Asep Herry Hernawan; Ahmad Fajar Fadillah; Deodatus Kolek (Curricula: Journal of Curriculum Development, 2025)
Indonesia, a nation rich in ethnic, cultural, and religious diversity, faces significant challenges in maintaining social harmony. Multicultural education is considered essential in fostering tolerance and intercultural understanding. This article examines the importance of incorporating multicultural values into Indonesia’s educational curriculum through the lens of Kenneth T. Henson, a curriculum theorist who emphasizes multiculturalism, constructivism, and educational reform. Utilizing a literature review method, this study analyzes the current state of multicultural education implementation, identifies the gap between practical application and its ideal curricular integration, and reflects on the relevance of Henson's theory within the Indonesian context. The findings reveal that despite supportive policies, field implementation remains constrained by limited teacher understanding, inadequate resources, and resistance to change. These challenges highlight the need for a more comprehensive and context-sensitive approach to multicultural curriculum planning and implementation. While Henson's framework offers valuable insights, its application in Indonesia requires thoughtful adaptation to local sociocultural realities, policy frameworks, and institutional capacities. The study concludes that integrating multiculturalism into Indonesia’s educational curriculum is both urgent and necessary, demanding strategic planning, institutional support, and ongoing professional development for educators.    Abstrak Indonesia dengan lanskap multietnis, multikultural, dan multi agama, menghadapi tantangan signifikan dalam menjaga harmoni sosial. Dalam konteks ini, pendidikan multikultural menjadi krusial untuk menumbuhkan toleransi dan pemahaman lintas budaya. Artikel ini mengeksplorasi urgensi integrasi nilai-nilai multikultural dalam kurikulum pendidikan nasional, khususnya melalui lensa pemikiran Kenneth T. Henson. Sebagai teoritikus kurikulum yang menekankan konstruktivisme, multikulturalisme, dan reformasi pendidikan, ide-ide Henson relevan untuk dikaji dalam konteks Indonesia. Menggunakan metode studi pustaka, penelitian ini menganalisis implementasi pendidikan multikultural saat ini, mengidentifikasi kesenjangan antara praktik dan idealitas, serta menyoroti relevansi pemikiran Henson bagi konteks lokal. Hasil kajian menunjukkan bahwa meskipun kebijakan mendukung telah ada, implementasi di lapangan masih terkendala oleh pemahaman guru yang terbatas, kurangnya sumber daya, dan resistensi terhadap perubahan. Oleh karena itu, diperlukan strategi yang lebih kontekstual dan komprehensif, bersama dengan adaptasi teori asing agar selaras dengan karakteristik sosiokultural Indonesia. Integrasi pendidikan multikultural membutuhkan dukungan kebijakan yang kuat dan pengembangan profesional guru yang berkelanjutan untuk mencapai tujuan harmoni sosial. Kata Kunci: kurikulum; multikulturalisme; pendidikan